PEMBELAJARAN SENI TARI BERBASIS PROJECT BASED LEARNING (PjBL) DI SMP NEGERI 41 PADANG - Dwi Latifatul Khairiyah; Hadi, Harisnal (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of dance appreciation learning based on the Project Based Learning (PjBL) model, as well as the involvement and abilities of ninth-grade students (Class IX/E) at SMP Negeri 41 Padang. The research employed a qualitative approach with a descriptive method, using observation, interviews, and documentation for data collection. The results show that PjBL-based learning was carried out through the stages of planning, implementation, project activities, and evaluation. At the beginning of the learning process, students’ participation and understanding were relatively low; however, they improved after engaging in activities such as observing dance performance videos, group discussions, and project presentations. The PjBL model encourages students to be more active and collaborative, although the learning process has not yet been fully optimal due to limited student focus at the initial stage and the less effective use of instructional modules.